Analisis Kualitas Pelayanan, Pengetahuan Dan Pemahaman Wajib Pajak Yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak: (Case Study Pada Pajak Kendaraan Bermotor Roda Dua Di Wilayah Kota Surabaya) - Karolina Setia; Herlambang Pudjo Santosa (CV. Ulil Albab Corp, 2024)
This study aims to analyze the factors influencing the compliance of motorcycle taxpayers in Surabaya. Taxpayer compliance is crucial for increasing local tax revenue, which contributes to regional development. The study employs a qualitative method with a survey approach, where data are collected through questionnaires distributed to motorcycle owners in Surabaya. The independent variables analyzed include tax knowledge, taxpayer awareness, perceptions of tax services, penalties and fines, and trust in the government. The data analysis is conducted using multiple linear regression to determine the effect of each variable on taxpayer compliance levels. The results indicate that tax knowledge, taxpayer awareness, and perceptions of tax services have a significant positive impact on taxpayer compliance. These findings suggest that to improve taxpayer compliance, the government should focus on enhancing tax education, improving the quality of tax services, and building public trust in the tax system